Resilience in Hostility: The Mental Health and Coping Mechanisms of Transgender Individuals in Georgia - Sordia,Mariam (2025)
Transgender individuals in Georgia face persistent stigma, violence, and limited institutional protections, yet little is known about how they cope with such hostility and what supports are available to them. Guided by Minority Stress Theory and coping research that distinguishes adaptive from maladaptive strategies, this study explored coping practices, social support, and mental health among transgender women in Georgia. Six participants were recruited through NGO networks and snowball sampling, and in-depth semi-structured interviews were conducted and thematically analyzed. Findings reveal that participants relied on a broad set of coping strategies, including problem-solving, peer and family support, creative or expressive outlets, and reframing hardship. Simultaneously, concealment, withdrawal, emotional coping, and substance use were reported as common but ambivalent strategies: while these approaches reduced immediate risks, they often carried longer-term psychological costs. Social support emerged as fragile and conditional. Families sometimes provided protection but typically avoided affirming identity; peer and chosen family networks offered moments of affirmation but were often shaped by mistrust and conflict. Across all accounts, participants reported ongoing mental health difficulties, such as depression, panic attacks, hypervigilance, and trauma-like symptoms, which were described not as episodic but as persistent states structuring daily life. These results highlight the limits of applying adaptive/maladaptive distinctions in high-stigma environments, where concealment or avoidance may serve as survival strategies. The study contributes region-specific insights to minority stress research and demonstrates the need for context-sensitive interventions that account for weak institutional protections and precarious support networks.
Keywords: transgender; coping; minority stress; mental health; Georgia